A highly stable MOF with F and N accessible sites for efficient capture and separation of acetylene from ternary mixtures. Issue 43 (28th October 2021) - Wang, Gang-Ding; Wang, Hai-Hua; Shi, Wen-Juan; Hou, Lei; Wang, Yao-Yu; Zhu, Zhonghua
Abstract : A stable Ni-MOF with high adsorption selectivity for C2 H2 was constructed by the strategy of incorporating active N and F sites in the porous surface, showing the dynamic separation of C2 H2 from binary and ternary mixtures in one-step. Abstract : Considering the important applications and purification requirement of C2 hydrocarbons in the industry, the separation of C2 in mixtures is a vital task. To achieve this goal, herein a new Ni 2+ -based metal–organic framework (MOF) has been solvothermally prepared by utilizing a tetrazolyl-carboxyl ligand and 4, 4′-bipyridine coligands as well as incorporating F − ions. The MOF shows a unique pillared-layer framework based on the novel metal–tetrazolate–carboxylate–fluorine chains, and possesses high chemical stability. Owing to the exposed adsorption sites of uncoordinated N atoms and F − ions in the channels, the MOF had high loadings for C2 H2 and selectivity for C2 H2 over C2 H4, C2 H6, CO2 and CH4 . Under ambient conditions, dynamic breakthrough experiments revealed that the MOF performs effective separation of C2 H2 from binary (C2 H2 –CH4, C2 H2 –C2 H6, C2 H2 –C2 H4, and C2 H2 –CO2 ) and ternary (C2 H2 –CO2 –CH4, C2 H2 –C2 H6 –CH4, C2 H2 –C2 H4 –CH4, and C2 H2 –C2 H4 –C2 H6 ) mixtures. The comparison based on the GCMC calculation revealed the crucial role of the accessible N and F sites for the selective capture of C2 H2 .